Penerimaan dan Penggunaan Layanan Mobile Banking Perbankan Syariah: Ekstensi Technology Acceptance Model - Heni Sukmawati; Joni Joni; Ari Farizal Rasyid; Mega Rachma Kurniaputri (ITB AAS INDONESIA Surakarta, 2021)
This study aims to analyze how the Islamic banking customer accepts mobile banking services and their behavior in using them. This study also aims to test the effect of Technology Acceptance Model (TAM) theory with spiritual motivation on customer intentions. This study uses quantitative methods with primary data obtained through the distribution of online questionnaires to Islamic banking customers who use mobile banking services. The data analysis technique used is Structural Equation Modeling – Partial Least Square (SEM-PLS). Islamic bank customers who receive and use mobile banking services are influenced by perceptions of convenience, perceived usefulness, attitudes, and intentions such as the Technology Acceptance Model theory. The level of spiritual motivation in this study can affect the intentions of Islamic bank customers as mobile banking users in Indonesia. This research is expected to be useful as additional information is needed to improve services for customers. This study examines Islamic bank customers who use mobile banking services and becomes the latest research after the merger of Islamic banks in Indonesia.